FGFR2‐Altered Gastroesophageal Adenocarcinomas Are an Uncommon Clinicopathologic Entity with a Distinct Genomic Landscape. (27th June 2019) - Klempner, Samuel J.; Madison, Russell; Pujara, Vivek; Ross, Jeffrey S.; Miller, Vincent A.; Ali, Siraj M.; Schrock, Alexa B.; Kim, Seung Tae; Maron, Steven B.; Dayyani, Farshid; Catenacci, Daniel V.T.; Lee, Jeeyun; et al.
Abstract: Background: With the exception of trastuzumab, therapies directed at receptor tyrosine kinases (RTKs) in gastroesophageal adenocarcinomas (GEA) have had limited success. Recurrent fibroblast growth factor receptor 2 (FGFR2) alterations exist in GEA; however, little is known about the genomic landscape of FGFR2 ‐altered GEA. We examined FGFR2 alteration frequency and frequency of co‐occurring alterations in GEA. Subjects, Materials, and Methods: A total of 6, 667 tissue specimens from patients with advanced GEA were assayed using hybrid capture‐based genomic profiling. Tumor mutational burden (TMB) was determined on up to 1.1 Mb of sequenced DNA, and microsatellite instability was determined on 95 or 114 loci. Descriptive statistics were used to compare subgroups. Results: We identified a total of 269 (4.0%) FGFR2 ‐altered cases consisting of FGFR2 ‐amplified (amp; 193, 72% of FGFR2 ‐altered), FGFR2 ‐mutated (36, 13%), FGFR2 ‐rearranged (re; 23, 8.6%), and cases with multiple FGFR2 alterations (17, 6.3%). Co‐occurring alterations in other GEA RTK targets including ERBB2 (10%), EGFR (8%), and MET (3%) were observed across all classes of FGFR2‐altered GEA. Co‐occurring alterations in MYC (17%), KRAS (10%), and PIK3CA (5.6%) were also observed frequently. Cases with FGFR2amp and FGFR2re were exclusively microsatellite stable. The median TMB for FGFR2 ‐altered GEA was 3.6 mut/mb, not significantly different from a median of 4.3 mut/mb seen in FGFR2 wild‐type samples. Conclusion: FGFR2 ‐altered GEA is a heterogenous subgroup with approximately 20% of FGFR2 ‐altered samples harboring concurrent RTK alterations. Putative co‐occurring modifiers of FGFR2‐directed therapy including oncogenic MYC, KRAS, and PIK3CA alterations were also frequent, suggesting that pretreatment molecular analyses may be needed to facilitate rational combination therapies and optimize patient selection for clinical trials. Implications for Practice: Actionable receptor tyrosine kinase alterations assayed within a genomic context with therapeutic implications remain limited to HER2 amplification in gastroesophageal adenocarcinomas (GEA). Composite biomarkers and heterogeneity assessment are critical in optimizing patients selected for targeted therapies in GEA. Comprehensive genomic profiling in FGFR2 ‐altered GEA parallels the heterogeneity findings in HER2 ‐amplified GEA and adds support to the utility of genomic profiling in advanced gastroesophageal adenocarcinomas. Abstract : Little is known about the genomic landscape of FGFR2‐altered gastroesophageal adenocarcinomas. This article attempts to bridge that gap, with a focus on concurrent alterations that may affect sensitivity to FGFR2‐directed therapies.